My friend Anne Frank : the inspiring and heartbreaking true story of best friends torn apart and reunited against all odds - Pick-Goslar, Hannah; Kraft, Dina (Little, Brown Spark, 2023)
"Firsthand account of a Holocaust survivor who knew Anne Frank"--